2022
DOI: 10.3389/fmicb.2022.913434
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella taylorii: A Model Organism for Studying Bartonella Infection in vitro and in vivo

Abstract: Bartonella spp. are Gram-negative facultative intracellular pathogens that infect diverse mammals and cause a long-lasting intra-erythrocytic bacteremia in their natural host. These bacteria translocate Bartonella effector proteins (Beps) into host cells via their VirB/VirD4 type 4 secretion system (T4SS) in order to subvert host cellular functions, thereby leading to the downregulation of innate immune responses. Most studies on the functional analysis of the VirB/VirD4 T4SS and the Beps were performed with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…B. henselae and B. taylorii were shown to translocate Bartonella effector protein D (BepD) via the VirB/VirD4 T4SS resulting in downregulation of pro-inflammatory cytokine ( e.g., TNF-α) secretion (36). However, mutant analysis indicated that B. taylorii must translocate at least one additional anti-inflammatory effector via its VirB/VirD4 T4SS that is different from the known Bep effectors (BepA-I) (37). As ByeA of B. taylorii inhibits p38 and JNK signaling, which might downregulate pro-inflammatory cytokine secretion as shown for other YopJ-family effectors, ByeA represents a candidate for this elusive immune-modulatory effector.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. henselae and B. taylorii were shown to translocate Bartonella effector protein D (BepD) via the VirB/VirD4 T4SS resulting in downregulation of pro-inflammatory cytokine ( e.g., TNF-α) secretion (36). However, mutant analysis indicated that B. taylorii must translocate at least one additional anti-inflammatory effector via its VirB/VirD4 T4SS that is different from the known Bep effectors (BepA-I) (37). As ByeA of B. taylorii inhibits p38 and JNK signaling, which might downregulate pro-inflammatory cytokine secretion as shown for other YopJ-family effectors, ByeA represents a candidate for this elusive immune-modulatory effector.…”
Section: Resultsmentioning
confidence: 99%
“…To test for functionality of a ByeA full-length fusion in this assay we introduced plasmids encoding HiBiT-FLAG (p control , negative control), HiBiT-FLAG-BepD (p bepD , bepD sequence of B. henselae , positive control (37)) or HiBiT-FLAG-ByeA (p byeA, byeA sequence of B. taylorii ) into the B. henselae effector-less Δ bepA-G background or the T4SS-deficient Δ virB4 background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HiBiT-tagged effector proteins were overexpressed in L. pneumophila using the plasmid pxDC61. One day prior to infection, RAW 264.7 macrophages expressing LgBiT [28,29] were seeded in a white clear-bottom 96 well cell culture plate (Greiner) at 8 x 10 4 cells/well. L. pneumophila strains were grown for 2-3 days on BCYE-Agar plates supplemented with “BCYE Growth Supplements” (Oxoid) and appropriate antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…To further elucidate the importance of the presence and localization of the C-terminal secretion signal of TMD-effectors for their translocation into host cells, we adapted a split-NanoLuc based translocation assay [28][29][30]. Plasmid-expressed HiBiT-effector-fusions were translocated by L. pneumophila into RAW 264.7 macrophages, stably expressing LgBiT in their cytoplasm and luminescence was assayed over time in a microtiter plate reader.…”
Section: A Cin Topology Facilitates Tmd-effector Translocationmentioning
confidence: 99%